Positive Emotions as Mediation Between Hedonic Shopping Motivations on Impulsive Buying Behavior of E-Commerce in Indonesia - Cahyani, Leni; Marcelino, Dandy (Department of Management, Faculty of Economics and Business, Brawijaya University, 2023)
In this modern age, the quick internet network indirectly produces a new phenomenon and lifestyle for those who frequently use the internet network. In this new era, enterprises or businesses that use the internet network are the birth of e-commerce. One example of e-commerce is the establishment of a marketplace or online store that introduces a new phenomena or a new way of life to the general public, namely online shopping. One of the Indonesian people's characteristics is a lack of planning (impulse buying). Impulse purchasing is defined as a strong want to acquire something right away that is more emotional than rational. Hedonic shopping motivation and positive emotions are two factors that might drive customers to make spontaneous purchases (impulsive buying). The elements listed above are things that might cause customers to make spontaneous purchases, and this is a fantastic chance for businesses to encourage consumers to be interested in making spontaneous purchases in e-commerce. Explanatory statistics with the SEM (Structural Equation Modeling) analytic technique are employed in this study, and the data was processed using SMART PLS 3.2.9. The researcher employed accidental sampling as sample strategy approach, resulting in 400 responses. This study finds that there are a mediating effect of positive emotional fulfillment on the relationship between hedonic shopping motivation and impulse buying, so implies that hedonic shopping motivations have indirect effect on e-commerce impulse buying through positive emotion.